2021
DOI: 10.1016/j.surg.2021.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of technical skills based on learning curve analyses in laparoscopic surgery training

Abstract: Background: Objective force-and motion-based assessment is currently lacking in laparoscopic skills curricula. This study aimed to evaluate the added value of parameter-based assessment and feedback during training. Methods: Laparoscopy-naïve surgical residents that took part in a 3-week skills training curriculum were included. A box trainer equipped with the ForceSense system was used for assessment of tissue manipulation-(MaxForce) and instrument-handling skills (Path length and Time). Learning curves were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…The number of cases performed (surgical volume) is one of the factors that unquestionably impact surgical efficiency [ 55 , 56 ].…”
Section: The Effect Of Surgical Expertise/learning Curvementioning
confidence: 99%
“…The number of cases performed (surgical volume) is one of the factors that unquestionably impact surgical efficiency [ 55 , 56 ].…”
Section: The Effect Of Surgical Expertise/learning Curvementioning
confidence: 99%
“…Trials exceeding the time limit were marked as "did not finish" and were excluded from the analysis. The ForceSense system recorded previously validated force-based parameters for the objective assessment of tissue handling skills [11][12][13][14].…”
Section: Main Study Parametersmentioning
confidence: 99%
“…2). The pre-test consisted of two previously validated fundamental laparoscopic skill (FLS) tasks [13][14][15]. Participants completed three trials per task as a baseline assessment.…”
Section: Study Protocolmentioning
confidence: 99%
“…A combination of performance parameters has been classified, representing tissue manipulation and instrument handling skills, which enables objective assessment of laparoscopic skills [16]. Our research group reported earlier successful implementation of objective performance parameters in basic laparoscopic skills training of first-year surgical residents, enabling objective assessment of learning curves [17].…”
mentioning
confidence: 99%
“…Objective assessment of the learning curve is essential to determine when proficiency levels have been acquired [17][18][19][20]. It is demonstrated that baseline performances of psychomotor ability uniquely predict the learning curve during laparoscopic skills training with virtual reality simulators [21,22].…”
mentioning
confidence: 99%